Australia`s National Rugby League's Player Development Framework: Evaluating strategies (2019) - Usher, W. (Journal of Human Sport & Exercise, 2021)
Rugby League (RL) is one of four football codes boasted across Australia; however, its participation rates are significantly lower when compared to other club sports, due to it being restricted to specific regions of Australia and viewed historically as a `male only` sport. This is of particular concern throughout the junior competitions. Therefore, it is imperative that the National Rugby League`s (NRL) future participation strategies adopt and reflect national / international `best practices`, so as to maintain and heighten positive and quality sporting opportunities, that are aimed to increase junior participation / retention, as well as build players` skills and personal development. The objective of this research is twofold, with the initial aim to demonstrate the clear alignment between the NRL`s Player Development Framework (PDF) and national / international movements concerning shifts in junior sporting models. A secondary aim is to demonstrate the impact and participants` satisfaction levels concerning seven initiatives. A quantitative approach was employed to investigate participants` (children, n = 916; adults, n = 20) reported experiences from their direct involvement across the seven initiatives. Nine hundred and thirty-six (936) participants (youth between 4 to over 15 years, n = 916), seniors aged between 20 and over 41 years, n = 20) had data collected from seven initiatives, that were implemented across the five testing centres (Ipswich, Gold Coast, Brisbane, Toowoomba and Victoria) in 2019. The initiatives were identified as being the: 1) RISE (n = 73), 2) League Tag (n = 330), 3) Tackle Safe (n = 168), 4) 18-Month Policy (n = 155), 5) Development Competition (n = 138), 6) Community League (n = 20) and 7) Weight Related (n = 52). Participants were only required to complete the one online survey associated with the initiative they were involved in. Spearman`s rho correlation (r) matrix was used to examine the strength of the association between variables, with p-values (p) employed to indicate statistically significant associations, at the one and two tail (p < .05* and p < .01**). Results have noticeably indicated that the full suite of programs have been well received and have gone to meet and support the PDF`s aims. Of particular note, is the high level of participants` agreement (p < .000) indicating that the programs significantly improved their level of:1) confidence, 2) involvement, and 3) enjoyment. Importantly, data indicates that participants who identified with the aforementioned levels of agreement, were significantly (p < .000) and positively correlated with 4) higher levels of willingness to recommend each of the programs to peers.